Numerical simulation of the influence of porosity on rock mechanical properties and energy dissipation - Wang, Yanwei; Qu, Kai; Fu, Jiang (Journal of physics. Conference series, 2025)
The ABAQUS software was used to simulate the triaxial compression test of rocks. Using Python programming scripts to achieve random deletion of units, thereby obtaining loading models with different porosities. Based on actual triaxial compression test data, numerical simulations are conducted to analyze the mechanical properties and energy dissipation evolution of rocks during loading. The results show that: ① With the increase of porosity, the elastic modulus, peak stress, and their corresponding internal energy and elastic strain energy all decrease linearly. ② When the pore volume in the rock is small, shear failure occurs, forming a distinct strain localization band. After the peak stress, the stress in the rock rapidly decreases, exhibiting brittle failure. Rocks with more pores exhibit multiple localized strain bands during failure, making them more fragmented. The stress after peak strength slowly decreases, exhibiting ductile failure characteristics. With the increase of porosity, the internal energy and elastic strain energy gradually decrease. After reaching the peak stress, the internal energy and plastic dissipation energy steadily increase, and the elastic strain energy is partially released. The release amount and release rate decrease due to the increase in rock porosity, and the severity of rock failure weakens. At the initial stage of loading, elastic deformation of the rock is the main cause, and at this time, the plastic dissipation energy is close to zero. When the stress reaches a certain value, the plastic dissipation energy slowly increases and rapidly increases near the peak stress until the rock fails.